Solution-Based Deposition of Transparent Eu-Doped Titanium Oxide Thin Films for Potential Security Labeling and UV Screening - Zhussupbekova, Ainur; Caffrey, David; Shvets, Igor (My University, 2020)
Transparent titanium oxide thin films attract enormous attention from the scientific community because of their prominent properties, such as low-cost, chemical stability, and optical transparency in the visible region. In this study, we developed an easy and scalable solution-based process for the deposition of transparent TiOx thin films on glass substrates. We showed that the proposed method is also suitable for the fabrication of metal-doped TiOx thin films. As proof-of-the-concept, europium Eu(III) ions were introduced into TiOx film. A photoluminescence (PL) study revealed that Eu-doped TiOx thin films showed strong red luminescence associated with 5D0!7Fj relaxation transitions in Eu (III).We found that prepared TiOx thin films significantly reduce the transmittance of destructive UV radiation; a feature that can be useful for the protection of photovoltaic devices. In addition, transparent and luminescent TiOx thin films can be utilized for potential security labeling.
PUBLISHED
Keywords: Transparent thin film; Titanium Oxide; Europium (III) doping; Security labeling; UV screening